Performance Modelling of Hybrid PQ-GPS Systems under Long-Range Dependent Network Traffic - Jin, Xiaolong; Min, Geyong (IEEE communications letters, 2007)
The hybrid PQ-GPS scheduling mechanism has been identified as a promising policy for the provisioning of differentiated quality-of-service (QoS) in modern communication networks. This paper proposes the first analytical performance model for the PQ-GPS scheduling mechanism subject to long-range dependent (LRD) network traffic. The core contribution is to develop a novel flow-decomposition approach that can equivalently divide the hybrid system into a group of single-server single-queue (SSSQ) systems in order to make the challenging problem of modelling the complex system tractable. The validity and accuracy of the model make it a practical and cost-effective tool for investigating the performance behaviour of the PQ-GPS system